STUDI PARAMETER BAKTERIOLOGI DI AIR SUNGAI ANAK SUNGAI DAS MARAM DAN DI SUMUR GALI SEKITARNYA DI KOTA JAMBI. - Guntar Marolop Saragih (Universitas Batanghari Jambi, 2014)
River which crosses the city that is also used by the inhabitants as a waste dump domestic and non-domestic waste, will make the quality is not in accordance with the quality standard. Similarly, if there dug wells around the river, the water can be affected by pollutants that exist in the river. One river that is in the middle of the city of Jambi is a tributary of the Maram watershed upstream on the road HOS Tjokroaminoto and enter the Batanghari river downstream. As a result of the activity of the surrounding population and environment sanitation is not good, visually creeks water quality Das Maram looks have been contaminated as indicated by the dark brown color, cloudy and smelly. To find out how much contamination, including E. coli and Coliformnya, we conducted laboratory tests. Including laboratory testing of existing wells dug around creeks. By knowing the parameters of physical, chemical and microbiological parameters of the E. coli and Coliform Das Maram creeks and wells dug in so that local people can react positively E. coli and coliform in the creeks Das Maram and dug wells around in the water above a predetermined quality standards. In water that is creeks Das Maram 2,300 MPN/100 ml for E. coli in the upstream and 3,110 MPN/100 ml in the lower reaches of creeks Das Maram. Coliform value of 3,100 MPN/100 ml for both upstream and downstream 4,300 MPN/100 ml. Microbiological parameters in dug wells showed in AB-1 and AB-2 in E. coli value of 20 MPN/100 ml. Coliform values in AB-1 at 70 MPN/100 ml and in the AB-2 by 90 MPN/100 ml.Keywords: bacteriology E. Coli, Coliform, creeks, wells dug.